Modeling geomagnetic cutoffs for space weather applications. Issue 7 (14th July 2015) - Kress, B. T.; Hudson, M. K.; Selesnick, R. S.; Mertens, C. J.; Engel, M.
Abstract Access of solar and galactic cosmic rays to the Earth's magnetosphere is quantified in terms of geomagnetic cutoff rigidity. Numerically computed grids of cutoff rigidities are used to model cosmic ray flux in Earth's atmosphere and in low Earth orbit. In recent years, the development of more accurate dynamic geomagnetic field models and an increase in computer power have made a real‐time data‐driven geomagnetic cutoff computation extending over the inner magnetosphere possible. For computational efficiency, numerically computed cutoffs may be scaled to different altitudes and directions of arrival using the known analytic variation of cutoff in a pure dipole magnetic field. This paper is a presentation of numerical techniques developed to compute effective cutoff rigidities for space weather applications. Numerical tests to determine the error associated with scaling vertical cutoff rigidities with altitude in a realistic geomagnetic field model are included. The tests were performed to guide the development of spatial grids for modeling cosmic ray access to the inner magnetosphere and to gain a better understanding of the accuracy of numerically modeled cutoffs.